Studying The Interaction of Laser with Human Tissue - Rizvi, Noor Kareem (Journal of Medical Genetics and Clinical Biology, 2024)
A laser is amplified light beam to emit radiation. these rays are used in surgery by accurately projecting laser light to remove diseased tissue or bleed blood vessels by heating the target cells until they explode. The laser is used medically under objective or complete anesthesia. There are many types of lasers such as carbon dioxide laser, YAG laser, and argon beam, and each type of laser has a specific use, and each type of surgery and tissue has a special color of laser light. the uses of the laser in the surgery are multiple. brain and liver tumors can be removed while not to damage the healthy tissue surrounding the tumors. Lymphatic vessels can be closed to reduce the spread of tumor cells and nerve endings to reduce pain after surgery, small bleeding blood vessels can be closed, in addition to removing warts and skin tumors. A general advantage of laser surgery is the absence of bleeding, reduced surgical infections, pain and wound size, and a short hospital stay. The recovery period after laser treatment depends on the type of pathological condition and the patient's health condition before treatment. In the end: the laser has successful surgical uses to obtain good results with minimal complications, and contrary to what is common, its medical uses are specific to certain diseases and not for all types of surgery. In addition, laser treatment requires modern and complex devices and experienced experts in their use